PENGARUH PEMBELAJARAN KEWIRAUSAHAAN TERHADAP MINAT MAHASISWA - Hateyong, Elisabet (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2018)
This study aims to determine the effect of entrepreneurship education on student entrepreneurrial intention in univercity. It shows when study was direct on enterpreneur practicum will be given motivation for the student in univercity. The results of entrepreneurship education have a significant influence on student entrepreneurial intentions. It shows that education metod, curiculum competation and how much time that used to study will be stimulation on student entrepreneurrial intention.